PENDAMPINGAN PENGEMBANGAN GEBLEK PEDAS PADA WIRAUSAHAPEMBUATAN GEBLEK DI DUSUN DUSUN BALONG V, DESA BANJARSARI, KECAMATAN SAMIGALUH, KULON PROGO, YOGYAKARTA - Susilo Wibisono (Asian Journal of Innovation and Entrepreneurship, 2015)
Geblek is a typical food of Kulon Progo made from starch or tapioca starch. Thisfood has a typical globular form a number eight shape and aslightly chewy texture. Geblekvery famous in Kulon Progo and surroundings, thus becoming one of the icon culinaryKulon Progo. It makes geblek is easy to find in Kulon Progo. As an entrepreneur geblek,innovate an obligation to succeed. A recent study byDeloitte Touche Tohmatsu Limitedrevealed that 78% of the "millennium generation" around the world think innovation isimportant to the development of an enterprise. It initiates the author to provide a newinsight and innovative idea for an entrepreneur geblek in Dusun Balong V, Kulon Progo,Yogyalarta, named Sutijem. The author's purpose is for develop Sutijem’s entrepreneurial.Innovative products such as spicy geblek will attract buyers and is successing Sutijem’sgeblek enterpreneurial.